Tinjauan Visual Subyek Foto dalam Karya Fotografi Potret Henri Cartie-Bresson dan Richard Avedon - Darmadi, Indra (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
Photography potrait is a photography field that highlight the character and traits of someone. In the world of photography there are two world leaders who are pioneers of photography in portrait photography, Henri Cartier-Bresson and Richard Avedon. Both have different theories in doing portrait photography. Conflicts that arise between the two is whether portrait photography should be done naturally or with posing. Of course, both have similarities photographic portraits, which portray someone in a work of portrait photography. This paper will discuss some of the work of portrait photography of Henri Cartier-Bresson and Richard Avedon, and compare the two works to find the answer to whether or not subjects to pose in a portrait photography.